2020
DOI: 10.1117/1.jatis.6.4.045002
|View full text |Cite
|
Sign up to set email alerts
|

Microelectromechanical deformable mirror development for high-contrast imaging, part 2: the impact of quantization errors on coronagraph image contrast

Abstract: Stellar coronagraphs rely on deformable mirrors (DMs) to correct wavefront errors and create high-contrast images. Imperfect control of the DM limits the achievable contrast, and therefore, the DM control electronics must provide fine surface height resolution and low noise. We study the impact of quantization errors due to the DM electronics on the image contrast using experimental data from the High Contrast Imaging Testbed facility at NASA's Jet Propulsion Laboratory. We find that the simplest analytical mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…demonstrated stable 5e-9 contrast in vacuum with a 32 × 32 MEMS mirror combined with a Vector Vortex Coronagraph (VVC) (Mawet et al, 2010). Bendek et al (2020) has developed and tested a CubeSat-scale MEMS deformable mirror controller that controls 32 × 32 actuators and survived flight on the PICTURE-C ballon.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated stable 5e-9 contrast in vacuum with a 32 × 32 MEMS mirror combined with a Vector Vortex Coronagraph (VVC) (Mawet et al, 2010). Bendek et al (2020) has developed and tested a CubeSat-scale MEMS deformable mirror controller that controls 32 × 32 actuators and survived flight on the PICTURE-C ballon.…”
Section: Discussionmentioning
confidence: 99%
“…al. [9] showed that to achieve 10 -10 raw contrast requires DM quantization at the 6-pm level. And, that DM minimum step height scales with the square root of the allocated contrast.…”
Section: Nm Rms) [4 5]mentioning
confidence: 99%